AI-Based Prophetic Curriculum in Islamic Religious Education: Integrating Humanization, Liberation, and Transcendence - Abdur Rosyid; Aris Munandar (Mudir: Jurnal Manajemen Pendidikan, 2026)
This research aims to formulate an ijtihad model of an Artificial Intelligence (AI)-based prophetic curriculum in Islamic Religious Education (PAI) from a curriculum management perspective. The study is motivated by the rapid transformation of education in the digital era, characterized by the widespread adoption of AI technologies that enhance learning efficiency and accessibility while simultaneously raising concerns related to ethics, dehumanization, and the erosion of educational values. This research employed a qualitative library research approach combined with normative-managerial conceptual analysis. Data were collected from peer-reviewed journal articles, scholarly books, and international reports published between 2013 and 2025, focusing on Islamic education, curriculum management, educational technology, and artificial intelligence. Sources were selected based on relevance, academic credibility, and contribution to discussions on prophetic education, AI integration, and curriculum development. The findings indicate that the development of an AI-based PAI curriculum requires a foundation of moral ijtihad as an ethical framework for responding to technological advancements. The proposed curriculum model integrates the prophetic values of humanization, liberation, and transcendence into the core functions of curriculum management, namely planning, organizing, implementation, and evaluation. The model offers several advantages over existing PAI curriculum frameworks by embedding prophetic values throughout the curriculum process, providing a structured mechanism for AI integration with ethical safeguards, and addressing contemporary challenges such as digital literacy, algorithmic bias, and technological dependency. These dimensions are often absent in conventional PAI curriculum models. Consequently, the proposed framework contributes to curriculum innovation and offers a conceptual basis for developing Islamic education policies and practices that balance technological advancement with character formation and spiritual development in the digital era.